Small heat shock proteins sequester misfolding proteins in near-native conformation for cellular protection and efficient refolding - Ungelenk, Sophia Maria; Moayed, Fatemeh; Ho, Chi-Ting; Grousl, Tomas; Scharf, Annette; Mashaghi, Alireza; Tans, Sander; Mayer, Matthias P.; Mogk, Axel; Bukau, Bernd (Nature Communications, 2016)
Small heat shock proteins (sHsps) contribute to cellular recovery and survival following stress causing elevated levels of misfolded or unfolded proteins. Here the authors demonstrate that sHsps function by maintaining aggregating proteins in close-to-native conformations to facilitate chaperone-mediated refolding.
Gesehen am 29.05.2020